FAKTOR-FAKTOR YANG MEMPENGARUHI BEHAVIOURAL INTENTION - Lily Purwianti; Karen Tio (Jurnal Manajemen Maranatha, 2017)
Internet is one of the electronic media with faster development than other electronic media. Survey proves that people use internet for entertainment, socialize, seeking information and purchasing goods or service through online. Survey's result also show online shopping trend keeps on increasing due to increase on consumer's need for e-commerce and other benefits that could be gained if consumer were buying things through online compared to buying directly. The purpose of this study was to evaluate the effect of e-service's elements such as e-service quality, customer satisfaction, attitude towards the website and behavioural intention to know how important is the factors of e-service in online shop's marketing strategy. The respondents in this study are customers that ever purchase from four Indonesia online shop website. The sample's criteria used in this study is non probability with purposive sampling method. The data analysis method are simple regression and multiple regression, Samples were collected by distributing 440 questionnaires in which the rate of return is 387. The results of this study indicate that e-service quality have a significant effect to customer satisfaction, e-service quality have significant effect to attitude towards the website, customer satisfaction have a significant effect to attitude towards the website, customer satisfaction have a significant effect to behavioural intention, brand image have a significant effect to customer satisfaction, brand image have a significant effect to behavioural intention and attitude towards the website have a significant effect to behavioural intention.Â Keywords: e-service quality, customer satisfaction, attitude towards the website, brand image dan behavioural intention.